A CROSS-SECTIONAL STUDY OF USING DENVER DEVELOPMENTAL SCREENING TEST II FOR DETECTING CEREBRAL PALSY EARLY IN YOUNG CHILDREN AND NEONATES AT PATNA MEDICAL COLLEGE AND HOSPITAL, PATNA, BIHAR. - Singh, Saumya; Kumari, Manisha; Narain, Bhupendra (Student's Journal of Health Research Africa, 2023)
Objectives This study aimed to assess and identify developmental delays in infants using the Denver Developmental Screening Test (DDST-II), examining potential contributing factors and offering recommendations for effective interventions. Methods The study employed a prospective cross-sectional design, enrolling 111 infants aged 0 months to 2 years attending a tertiary care center for 2 years. Denver Developmental Screening Test (DDST-II) was administered, and infants were followed up for three consecutive months to assess developmental milestones and potential contributing factors. Results In the study encompassing 111 infants, 6.4% demonstrated delayed development, 7.8% exhibited doubtful delays, and 85.8% were considered normal. Notably, 25% of cases with developmental concerns had a history of preterm birth, 35% were of low birth weight, and 30% were delivered via cesarean section. Furthermore, 100% detection rates for delayed development were observed in infants aged 13-24 months. Conclusion The current study underscores a notable prevalence of developmental delays among infants, emphasizing the critical importance of early detection and intervention. The multifactorial nature of contributing elements, including preterm birth and low birth weight, highlights the complexity of developmental challenges. The study's findings contribute valuable insights into developmental patterns, supporting the need for broader research and targeted interventions. Recommendation The study recommends further research with larger and more diverse samples to enhance generalizability. Additionally, exploring the effectiveness of tailored interventions for developmental delays is crucial for optimizing infant development.